Mathematical modeling of the manufacturing sector of energy-dependent economy - Гайдучок, Олена Василівна (Technology audit and production reserves, 2015)
The economy, the production of which is aggregated in two sectors, is considered in the article. The first sector is produced a uniform final product, part of which is used as a consumer product to the public, and some – like fund-creating product to create capacity in both sectors. The second sector is produced a uniform product – the energy, part of which is spent in the first sector of the production process, and some – for final human consumption. The technology that used in the first and second sectors and production capacity of manufacturers are described. Using a systematic approach it is built the mathematical models for recording the capacity of first and second sector. The research results can be used to forecasting the development of energy-dependent economy by changing the price of imported energy and efforts to control the parameters of the economy.